Stakeholder Involvement in Inclusive Campus Services for Students with Disabilities in Indonesia - Gilang Wilmantara; Bimantara Nur Alim (Yayasan Ilomata, 2026)
This study aims to describe several relevant services that need to be supported by stakeholders to support the inclusion of people with disabilities in higher education in Indonesia. The method used in this research is a descriptive qualitative method. Using the secondary data obtained from news, journals, published articles, and government survey results, which were reviewed based on the conditions of several campuses in Indonesia, with a minority of disabled students. The results of the study indicate that the implementation of disability inclusion in Indonesian universities still faces significant challenges, particularly in terms of infrastructure, human resource readiness, and policy implementation. Some universities have begun efforts through the establishment of disability service units, training to provide disability services, and the provision of accessible facilities. The campuses in question which has implemented the policy that are leaning more into disability-friendly practices, has proved to be more inclusive within the universities civitas in Indonesia. However, service indicators that serve as benchmarks for inclusivity have not yet been consistently applied. The findings of this research reveal that disability inclusion in Indonesian higher education institutions has not been implemented systematically. Although some institutions have made initial efforts to adopt an inclusive approach, there are no standardized evaluation indicators to assess the achievements and quality of services provided. The absence of these standards results in inclusion policies and practices being implemented without a consistent direction.